The effectiveness of emotion-oriented couple therapy on marital burnout and resilience of young couples - Mehdigholi, Mohammadreza; Dokanehi Fard , Farideh; Jahangir , Pantea (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Due to the lack of experience and resilience in marital conflicts, young couples are more exposed to marital heartbreak and as a result tend to divorce. This research was conducted with the aim of determining the effectiveness of emotion-focused couple therapy on marital burnout and resilience of young couples. Methods: A quasi-experimental research method was used with a pre-test-post-test design with a control group. 30 couples (30 men and 30 women) were selected from the statistical population of young couples who referred to family counseling centers in the 1st district of Tehran using the available sampling method and were replaced in two experimental and control groups using a random method. The research tools were marital burnout (Pines, 1996), resilience (Connor & Davidson, 2003). The research findings were analyzed using SPSS version 23 software and analysis of variance with repeated measurements. Results: The results showed that emotional couple therapy has a significant and stable effect on reducing marital boredom and increasing resilience of young couples (p